Campylobacter concisus Genomospecies 2 Is Better Adapted to the Human Gastrointestinal Tract as Compared with Campylobacter concisus Genomospecies 1 - Wang, Yiming; Liu, Fang; Zhang, Xiang; Chung, Heung Kit Leslie; Riordan, Stephen M.; Grimm, Michael C.; Zhang, Shu; Ma, Rena; Lee, Seul A.; Zhang, Li (Frontiers in Physiology, 2017)
ABSTRACT Campylobacter concisus was previously shown to be associated with inflammatory bowel disease including Crohn's disease (CD) and ulcerative colitis (UC). C. concisus has two genomospecies (GS). This study systematically examined the colonization of GS1 and GS2 C. concisus in the human gastrointestinal tract. GS1 and GS2 specific polymorphisms in 23S rRNA gene were identified by comparison of the 23S rRNA genes of 49 C. concisus strains. Two newly designed PCR methods, based on the polymorphisms of 23S rRNA gene, were developed and validated. These PCR methods were used to detect and quantify GS1 and GS2 C. concisus in 56 oral and enteric samples collected from the gastrointestinal tract of patients with IBD and healthy controls. Meta-analysis of the composition of the isolated GS1 and GS2 C. concisus strains in previous studies was also conducted. The quantitative PCR methods revealed that there was more GS2 than GS1 C. concisus in samples collected from the upper and lower gastrointestinal tract of both patients with IBD and healthy controls, showing that GS2 C. concisus is better adapted to the human gastrointestinal tract. Analysis of GS1 and GS2 composition of isolated C. concisus strains in previous studies showed similar findings except that in healthy individuals a significantly lower GS2 than GS1 C. concisus strains were isolated from faecal samples, suggesting a potential difference in the C. concisus strains or the enteric environment between patients with gastrointestinal diseases and healthy controls. This study provides novel information regarding the adaptation of different genomospecies of C. concisus in the human gastrointestinal tract.